Patterns Of Smartphone Use Among University Students In Jordan - أبو صليح، محمد; العدوان، نايل طلال; اليحيى، محمد; عمارنه، باسل; خضر، يوسف صالح (اتحاد الاطباء النفسانيين العرب, 2019)
تهدف الدراسة إلى وصف أنماط وأساليب سلوك استخدام الهاتف الذكي بين طلاب الجامعات في الأردن. الطرق: العينة العشوائية مكونة من (1005) طالب (412 ذكور، 593 إناث)، كانوا مسجلين في الكليات الصحية في جامعة العلوم والتكنولوجيا الأردنية في الفصل الدراسي الثاني من العام الأكاديمي 2017/2018 أنهي الاستبيان 918 مشارك (541 من الإناث، 377 من الذكور، متوسط العمر 19 ± 1.6 سنة) أنشئ استبيان مكون من جزئيين، الجزء الأول عن البيانات الديموغرافية والجزء الثاني عن سلوك استخدام الهاتف الذكي. النتائج: ما مجموعه 547 (59.6 %) طالب أقروا بأنهم يمضون أقل من 5 ساعات يوميا على هواتفهم الذكية، 317 (%40.4) أقروا باستخدام هواتفهم الذكية لمدة تزيد عن خمس ساعات يوميا. حوالي ثلاث أرباع الطلبة أخبروا أنهم يتفقدون هواتفهم الذكية بمعدل مرة واحدة أو أكثر كل نصف ساعة. الوسط الحسابي (الانحراف المعياري) للوقت المصروف على الهواتف الذكية بالساعات كان 5.9 (3.7) وهذه الأوساط الحسابية وجدت بأنها تختلف إحصائيا حسب الجنس والعمر وسنوات الدراسة، بينما امتلاك حزمة أنترنت لم يؤثر على وقت الاستخدام اليومي. الاستنتاجات: جاءت ملاحظاتنا داعمة لازدياد استخدام الهواتف الذكية في الأردن بين طلاب الجامعات، وكان الاستخدام الأكثر شيوعا هو للتواصل مع الأهل والأصدقاء ثم للبحث عن المعلومات ثم لتفقد وسائل التواصل الاجتماعي. وكان أكثر المواقف التي يتم استخدام الهاتف الذكي خلالها هي عند الشعور بالملل.
The intimate contact people have with smartphones has a strong impact on behavior and on the physical and psychological well-being of those who use them. Aim: The current study described smartphone usage patterns and practices among university students in Jordan. Methods: A random sample of N=1005 students (n=412 men; n=593 women) were recruited to the study. All participants were registered in the health faculties at the Jordan University of Science and Technology (JUST) for the second semester of the academic year 2016/2017. N=918 participants (n=541 women, n=377 men; M=19.8, SD=1.6 years) completed a two-part questionnaire. Part one assessed demographic data; the second surveyed smartphone usage. Independent t-test and one-way ANOVA were used to test the significance of differences between means. Results: A total n=547 (59.6%) students reported spending less than five hours on the smartphone daily, n=371 (40.4%(reported spending more than five hours. About three quarter of students (70.7%) reported checking their smartphone every 30 minutes or more. The mean (SD) of daily time spent on smartphones in terms of hours was 5.9 (3.7); these means were found to be statistically different according to gender, age and years of education while having an internet package did not impact the daily time use. Conclusions: Findings support the view that smartphone usage is increasing among university students in Jordan. Communicating with family and friends followed by searching for information and checking social media were the most commonly described uses. The most common situational factor for using smartphones was boredom.
Keywords: الأردن -- طلاب الجامعات -- الهواتف الذكية -- وسائل التواصل الاجتماعي